Clerodendrumol, A New Triterpenoid from Clerodendrum yaundense Gürke (Lamiaceae). Issue 2 (February 2016) - Awouafack, Maurice D.; Aimaiti, Simayijiang; Tane, Pierre; Morita, Hiroyuki
Abstract: A new lupane‐type triterpene named clerodendrumol (1 ), i.e., (16 α )‐lupa‐12, 20(29)‐dien‐16‐ol, together with five known compounds, octacosa‐(5 Z, 9 Z ) ‐ dienoic acid (3 ), tetracosanoic acid (4 ), genkwanin (5 ), (12 S )‐hydroxyoctadeca‐(9 Z, 13 E, 15 E )‐trienoic acid (6 ), and (9 S )‐hydroxyoctadeca‐(10 E, 12 E )‐dienoic acid (7 ), were isolated from the twigs of Clerodendrum yaundense. O ‐Acetylclerodendrumol (2 ), a derivative of1, was prepared by a standard acetylation procedure applied to compound1 . The structure of the new compound was elucidated using spectroscopic analysis (NMR and MS) data, and chemical conversions (acetylation and deacetylation). The human breast cancer cell line (MDA‐MB‐231) was sensitive to all test samples, and clerodendrumol (1 ) as well as its derivative2 had good activity ( IC 50 values 7.5 and 13.2 μM ). Genkwanin (5 ) exhibited strong activity on HeLa cell line with IC 50 7.8 μM . Abstract :